Variability in opioid prescription monitoring and evidence of aberrant medication taking behaviors in urban safety-net clinics - Lange, Allison (Pain, 2015)
Little is known about variability in primary care providers’ (PCPs) adherence to opioid-monitoring guidelines for patients. We examined variability of adherence to monitoring guidelines among PCPs and ascertained the relationship between PCP adherence and opioid misuse by their patients. We included primary care patients receiving long-term opioids (≥3 prescriptions within 6 months) for chronic noncancer pain and PCPs with ≥4 eligible patients. We examined guideline adherence using: (1) electronic health record documentation of opioid treatment agreement, (2) past-year urine drug screen (UDS), and (3) evidence of misuse through early refills (≥2 opioid prescriptions written 7–25 days after the previous prescription). Covariates included morphine equivalent daily opioid medication dose (MED, >50 mg/d vs ≤50mg/d). Multilevel regression models assessed variability among PCPs, and odds ratios examined associations among patient-level binary outcomes. Sixty-seven PCPs prescribed opioids to 1546 patients. Significant variability was found between PCPs in use of agreement (variance = 1.27, P<0.001), UDS (variance = 1.75, P <0.001), and early refills (variance = 0.29, P = 0.002). Primary care providers had a mean of 48% of patients with agreement (range, 9%–84%), 56% with ≥1 UDS (range, 7%–91%) and 36% with early refills (range, 19%–60%). High MED among patients was associated with increased odds of agreement (1.93, confidence interval [CI], 1.53–2.44), UDS (2.65, CI: 2.06–3.41), and early refill (2.92, CI: 2.30–3.70). Primary care providers varied significantly in adherence to opioid prescription guidelines. Increased patient risk was associated with increased monitoring and with greater misuse. Future work should study system-level interventions to enable clinical monitoring and support opioid guideline adherence.